Magnetic field as an environmentally friendly tool increases the effectiveness of pesticides: A case study of acaricide spirodiclofen against Tetranychus urticae Koch (Acari: Tetranychidae) - Behnam Nezhadakbarimahani; Aurang Kavousi; Jaefar Nikbakht; Mohammad Hossein Rasoulifard ‎ (Persian Journal of Acarology)
Applying reduced doses of pesticides has advantages such as resistance management, environmental pollution reduction, and control costs. Very few studies show that passing the water used for pesticide applications through a magnetic field can improve the pesticides' efficiency. In this study, the effect of a magnetic field on the acaricidal activity of spirodiclofen was evaluated against Tetranychus urticae. Treatments included distilled water and well water for preparing the suspensions after passing through a constant magnetic field of 0.42 Tesla. Furthermore, additional treatments were made by passing the prepared suspensions through the magnetic field. Mites were counted right before the sprays on days 7, 14, and 21. The treatment efficiencies were calculated by using the Henderson-Tilton formula. Except for 2 of 12 cases in which the efficiencies were negative, in the rest of the experiments, the magnetic field enhanced the efficiency of the studied acaricide. The highest values were recorded for two treatments including magnetizing the mixture of well water and acaricide treatment and magnetized distilled water plus acaricide treatment between days 7 to 21 (approximately 77 %). This study suggests the usefulness of magnetic fields as an environmental-friendly method to increase the effectiveness of the studied plant protection agent.